Integration of an RF coil and commercial field camera for ultrahigh‐field MRI. Issue 5 (21st December 2021) - Gilbert, Kyle M.; Dubovan, Paul I.; Gati, Joseph S.; Menon, Ravi S.; Baron, Corey A.
Abstract: Purpose: To develop an RF coil with an integrated commercial field camera for ultrahigh field (7T) neuroimaging. The RF coil would operate within a head‐only gradient coil and be subject to the corresponding design constraints. The RF coil can thereafter be used for subject‐specific correction of k ‐space trajectories—notably in gradient‐sensitive sequences such as single‐shot spiral imaging. Methods: The transmit and receive performance was evaluated before and after the integration of field probes, whereas field probes were evaluated when in an optimal configuration external to the coil and after their integration. Diffusion‐weighted EPI and single‐shot spiral acquisitions were employed to evaluate the efficacy of correcting higher order field perturbations and the consequent effect on image quality. Results: Field probes had a negligible effect on RF‐coil performance, including the transmit efficiency, transmit uniformity, and mean SNR over the brain. Modest reductions in field‐probe signal lifetimes were observed, caused primarily by nonidealities in the gradient and shim fields of the head‐only gradient coil at the probe positions. The field‐monitoring system could correct up to second‐order field perturbations in single‐shot spiral imaging. Conclusion: The integrated RF coil and field camera was capable of concurrent‐field monitoring within a 7T head‐only scanner and facilitated the subsequent correction of k ‐space trajectories during spiral imaging.